2005
DOI: 10.2174/156720505774330555
|View full text |Cite
|
Sign up to set email alerts
|

Chitin-like Polysaccharides in Alzheimers Disease Brains

Abstract: The role of polysaccharides in the pathogenesis of Alzheimer disease (AD) is unclear. However, in light of studies indicating impaired glucose utilization in AD and increased activation of the hexosamine pathway that is seen with hyperglycemia, in the brains of patients with AD, aberrantly high levels of glucosamine may result in synthesis of glucosamine polymers such as chitin, a highly insoluble polymer of N-acetyl glucosamine, linearized by beta1-4 linkages. To examine this further, we studied brain tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 8 publications
1
54
1
Order By: Relevance
“…33,34,40,41 In this light, the high Chit expression -as demonstrated also by Di Rosa and collaborators 42 -may have a dual role: it either represents a mere epiphenomenon of a strong macrophagemicroglia activation due to β-amyloid deposition, or reflects a scavenging protective immune activity against potentially pathogenic chitin-like glucosamine polymers. 33 Thus, encouraged by these findings, we performed an immunocytochemistry study in order to explore the presence of chitin-like substances within AD, MS and healthy control (HC) brains. On the one hand, we could confirm the presence of abundant chitin-like substances in the brains of AD patients, which may well relate to the detection of peripheral Chit activity.…”
Section: Microglia and Chitotriosidase In Multiple Sclerosismentioning
confidence: 87%
See 4 more Smart Citations
“…33,34,40,41 In this light, the high Chit expression -as demonstrated also by Di Rosa and collaborators 42 -may have a dual role: it either represents a mere epiphenomenon of a strong macrophagemicroglia activation due to β-amyloid deposition, or reflects a scavenging protective immune activity against potentially pathogenic chitin-like glucosamine polymers. 33 Thus, encouraged by these findings, we performed an immunocytochemistry study in order to explore the presence of chitin-like substances within AD, MS and healthy control (HC) brains. On the one hand, we could confirm the presence of abundant chitin-like substances in the brains of AD patients, which may well relate to the detection of peripheral Chit activity.…”
Section: Microglia and Chitotriosidase In Multiple Sclerosismentioning
confidence: 87%
“…13,14,27,51,57 If β-amyloid has a pathogenic and not only a pathognomonic role in AD, the role of chitin may be that of favouring and accelerating its detrimental deposition. 33 Recently, Castellani and colleagues 34 suggested that chitin-like polysaccharides within the AD brain could provide a scaffolding for β-amyloid deposition and that glucosamine may therefore facilitate the process of amyloidosis. This finding may support the hypothesis that an imbalance between glucosamine polymerisation and degradation in AD favours fibril formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations